Analisis Perbandingan Komunikasi Satelit Frekuensi C-Band Dan Ka-Band Di Indonesia - Tanridio Silviati Delfina Abdurrahman; Salmiah Salmiah; Saidah Suyuti (PROtek : Jurnal Ilmiah Teknik Elektro, 2020)
This paper analyzes the comparison of data communications using GEO satellites between C-band and Ka-band frequencies in Indonesia which has a tropical rain climate. The data communication uses QPSK modulation on the path of four earth stations by paying attention to six variations of observation time. Parameters, C/ N, Eb/No and link margins, are applied to indicate the communication performance. This study shows that C-band satellite communication can be implemented for all conditions, whereas in Ka-band the success of communication transfer cannot be accessed by all observation times.Â